A multifunctional polymeric nanofilm with robust chemical performances for special wettability. Issue 9 (15th February 2016) - Wang, Yabin; Lin, Feng; Dong, Yaping; Liu, Zhong; Li, Wu; Huang, Yudong
Abstract : A multifunctional polymeric nanofilm of a triazinedithiolsilane compound, which can protect metallic substrates and activate the corresponding surface simultaneously, is introduced onto a copper mesh surface via facile solution-immersion approaches. Abstract : A multifunctional polymeric nanofilm of a triazinedithiolsilane compound, which can protect metallic substrates and activate the corresponding surface simultaneously, is introduced onto a copper mesh surface via facile solution-immersion approaches. The resultant interface exhibits hydrophilic features due to the existence of silanol groups (SiOH) outward and has the potential to act as a superhydrophilic and underwater superoleophobic material. As the polymeric nanofilm atop the copper mesh is modified with long-chain octadecyltrichlorosilane (OTS), the functionalized surface becomes superhydrophobic and superoleophilic. The OTS-modified polymeric nanofilm shows outstanding chemical durability and stability that are seldom concurrently satisfied for a material with special wettability, owing to its inherent architecture. These textures generate high separation efficiency, durable separation capability and excellent thermal stability. The protective ability, originating from the textures of the underlying cross-linked disulfide units (–SS–) and siloxane networks (SiOSi) on the top of the nanofilm, prolongs the chemical durability. The activating capability stemming from the residual SiOH groups improves the chemical stability as a result of the chemical bonds developed by these sites. The significant point of this investigation lies in enlightening us on the fabrication of multifunctional polymeric nanofilms on different metal surfaces using various triazinedithiolsilane compounds, and on the construction of interfaces with controllable wettable performances in demanding research or industrial applications.